Using Rapid City Surveys to Inform Municipal Social Policy: An Application in Cali, Colombia - Hentschel, Jesko (World Bank, Washington, D.C., 2013)
Many developing countries assign local governments increasing responsibilities in fighting poverty. This requires local social policy to go beyond the execution of centrally designed and funded education and health programs. Hence, local governments and their partners have both an opportunity and a need to analyze key local bottlenecks for poverty reduction and social development. Drawing on an example from Cali, Colombia, The author describes a tool for such policy formulation at the local level-a rapid city household survey. Although the survey uses pre-coded and closed- ended questions, it is contextual in the sense that it is tailor-made to social and economic conditions in Cali. The survey places particular emphasis on collecting key quantitative information, such as household welfare and service access, as well as qualitative information, such as service evaluations and population priorities. Combining the quantitative and qualitative data allows, for example, the mapping of population budget priorities or service satisfaction levels by welfare group. Rapid city household surveys could provide an important tool for the development of local social policies.